Self-healing of fractured GaAs nanowires. - Wang, Y; Joyce, H; Gao, Q; Liao, X; Tan, H; Zou, J; Ringer, S; Shan, Z; Jagadish, C (2011)
In-situ deformation experiments were carried out in a transmission electron microscope to investigate the structural response of single crystal GaAs nanowires (NWs) under compression. A repeatable self-healing process was discovered in which a partially fractured GaAs NW restored its original single crystal structure immediately after an external compressive force was removed. Possible mechanisms of the self-healing process are discussed.